Biomechanical properties of common graft choices for anterior cruciate ligament reconstruction: A systematic review. (May 2022) - Malige, Ajith; Baghdadi, Soroush; Hast, Michael W.; Schmidt, Elaine C.; Shea, Kevin G.; Ganley, Theodore J.
Abstract: Background: This systematic review explores the differences in the intrinsic biomechanical properties of different graft sources used in anterior cruciate ligament (ACL) reconstruction as tested in a laboratory setting. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, two authors conducted a systematic review exploring the biomechanical properties of ACL graft sources (querying PubMed, Cochrane, and Embase databases). Using the keywords "anterior cruciate ligament graft, " "biomechanics, " and "biomechanical testing, " relevant articles of any level of evidence were identified as eligible and included if they reported on the biomechanical properties of skeletally immature or mature ACL grafts solely and if the grafts were studied in vitro, in isolation, and under similar testing conditions. Studies were excluded if performed on both skeletally immature and mature or non-human grafts, or if the grafts were tested after fixation in a cadaveric knee. For each graft, failure load, stiffness, Young's modulus, maximum stress, and maximum strain were recorded. Findings: Twenty-six articles were included. Most studies reported equal or increased biomechanical failure load and stiffness of their tested bone-patellar tendon-bone, hamstring, quadriceps, peroneus longus, tibialis anterior and posterior, Achilles, tensor fascia lata, and iliotibial band grafts compared to the native ACL. All recorded biomechanical properties had similar values between graft types. Interpretation: Most grafts used for ACL reconstruction are biomechanically superior to the native ACL. Utilizing a proper graft, combined with a standard surgical technique and a rigorous rehabilitation before and after surgery, will improve outcomes of ACL reconstruction. Highlights: We explore intrinsic properties of Anterior Cruciate Ligament graft sources. Most grafts are equal or superior to the native Anterior Cruciate Ligament. All 5 biomechanical properties recorded had similar values between graft types.